2010
DOI: 10.1002/jat.1616
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of (−)‐cubebin in somatic cells of mice

Abstract: (-)-Cubebin belongs to the dibenzylbutyrolactone lignan group, which is widely distributed in the plant kingdom. Because this compound shows interesting biological activities, it is extremely important to evaluate its possible genotoxic activity to allow its safe use in humans. Thus, the present study was performed to investigate the genotoxicity potential activity of (-)-cubebin assessed by two assays: micronucleus in bone marrow cells and comet test in peripheral blood leukocytes of Swiss mice. In the (-)-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Taken together, these data suggest that at concentrations tested, (-)-cubebin did not produce clastogenic or aneugenic damage in HT29 cells. Our data are contradictory to those of Maistro et al (2011), who observed a clastogenic effect of (-)-cubebin at 500 and 2000 mg/kg in murine bone-marrow cells. In the same study, no genotoxic effect was observed in peripheral blood cells of mice treated with (-)-cubebin at a concentration of 250 mg/kg for 24 h and at concentrations of 500 mg/kg and 2000 mg/kg for 4 h.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest that at concentrations tested, (-)-cubebin did not produce clastogenic or aneugenic damage in HT29 cells. Our data are contradictory to those of Maistro et al (2011), who observed a clastogenic effect of (-)-cubebin at 500 and 2000 mg/kg in murine bone-marrow cells. In the same study, no genotoxic effect was observed in peripheral blood cells of mice treated with (-)-cubebin at a concentration of 250 mg/kg for 24 h and at concentrations of 500 mg/kg and 2000 mg/kg for 4 h.…”
Section: Discussioncontrasting
confidence: 99%
“…Because (-)-cubebin displays therapeutic promise and serves as the starting point for the production of more effective synthetic derivatives, studies that seek to evaluate possible harmful effects on cells are important to determine the safety profile of (-)-cubebin. Maistro et al (2011) found that (-)-cubebin produced genotoxic effects in Swiss mice by performing micronucleus (MN) assays on bone marrow cells and comet assays on peripheral blood lymphocytes (PBL). These data showed that caution is necessary and that more studies are needed to assess the risks of (-)-cubebin ingestion before it is prescribed to humans.…”
mentioning
confidence: 99%
“…Published reports on the mutagenicity of (À)-cubebin are scarce. Maistro et al (2011) observed a clastogenic effect in murine bone marrow cells treated with 500 mg/kg and 2000 mg/kg (À)cubebin. In the same study, no genotoxic effect was observed in the peripheral blood cells of mice treated with 250 mg/kg (À)-cubebin for 24 h and at concentrations of 500 mg/kg and 2000 mg/kg for 4 h.…”
Section: Discussionmentioning
confidence: 98%
“…Seeded 96-well culture plates (2.5 Â 10 4 cells/well) were incubated at 37 8C for 24 h. After this period, the following treatments were administered for 24, 48 and 72 h: control (0.25% DMSO); cytotoxicity inducer (18.4 mM doxorubicin); and (À)cubebin at 0.028 mM, 0.28 mM, 2.8 mM, 28 mM and 280 mM. The selection of concentrations used in MTT assay was based on in vivo study of Maistro et al (2011). DMSO at a concentration of 0.25% was also administered to wells containing culture medium alone (no cells) for use as a ''blank'' control.…”
Section: Mtt Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation